Pengaruh Strategi Pembelajaran Fisika Berbasis Website Terhadap Hasil Belajar Pada Siswa yang Memiliki Selfregulated Learning (SRL) yang Berbeda - Mohammad Djamil M. Nur (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2017)
This study aims to examine differences in learning outcomes between groups of students taught by website-based physics learning and groups of students taught video-based learning. Furthermore, to determine the differences in learning outcomes between groups of students who have different self-regulated learning and to explain the interaction between website-based physics learning and self-regulated learning on learning outcomes. The research design was a quasi-experimental study with a 2X2 factorial design. The research subjects consisted of two groups taught by website-based physics learning with video-based physics learning. The instrument used to measure student learning outcomes is a test of learning outcomes, while to determine self-regulated learning (SRL) uses a self-regulated learning (SRL) questionnaire. The results of the analysis show that there are differences in learning outcomes between groups of students taught by website-based physics learning and groups of students taught by Video-Based Learning. The test results showed that the learning outcomes among the group of students who studied physics based on the website had a higher score of 7.82% compared to the physics learning group based on the video. There are differences in learning outcomes between groups of students who have different self-regulated learning. The test results showed that the learning outcomes between groups of students with high self-regulated learning had a value of 19.53% higher than those with low self-regulated learning. There is an interaction between web-based physics learning and self-regulated learning on learning outcomes.